Humidity and low pH boost occurrence of Onygenales fungi in soil at global scale. (April 2022) - Coleine, Claudia; Selbmann, Laura; Guirado, Emilio; Singh, Brajesh K.; Delgado-Baquerizo, Manuel
Abstract: Soils are important reservoirs for potential human pathogens and opportunistic fungi such as the dermatophyte or dimorphic fungi in the order Onygenales. In soils, these taxa are decomposers but many of them have the potential to cause respiratory and skin diseases in humans and, in some cases, systemic infections. Even so, the factors that determine the biogeography and ecology of order Onygenales remain largely undocumented. To address this knowledge gap, we surveyed members of Onygenales from topsoil fungal communities at 235 sites across six continents and provided a first global atlas. We retrieved 4.3% of the total fungal sequences (∼420 Onygenales) across nine biomes ranging from deserts to tropical forests. This work advances our knowledge on the ecology and global distribution of order Onygenales and suggests the hypothesis that wet and acid soils support the larger proportions of these fungi, while their richness is constrained by aridity. Highlights: Soils support a significant portion of Onygenales fungi, including potential human pathogens. Aridity was a key factor affecting Onygenales community composition across the globe. Wet and acid soils support the larger proportions and richness of Onygenales globally.